2006
DOI: 10.1111/j.1572-0241.2006.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Count/Spleen Diameter Ratio for the Noninvasive Diagnosis of Esophageal Varices: Results of a Multicenter, Prospective, Validation Study

Abstract: The platelet count/spleen diameter ratio may be proposed as a safe and reproducible means to improve the management of cirrhotic patients who should undergo screening endoscopy for EV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
185
4
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(204 citation statements)
references
References 37 publications
10
185
4
5
Order By: Relevance
“…D'Amico and Morabito 8 summarized these studies, and an ROC showed that none of these markers were reliable for the presence of GEV. In a recent multicenter, crosssectional study conducted by Giannini et al 22 using a novel PLT to spleen diameter ratio cutoff of 909, the diagnostic accuracy for GEV was 86% with a negative predictive value of 87%. The accuracy was maintained when the severity and etiology of the disease subgroups were considered.…”
Section: Discussionmentioning
confidence: 99%
“…D'Amico and Morabito 8 summarized these studies, and an ROC showed that none of these markers were reliable for the presence of GEV. In a recent multicenter, crosssectional study conducted by Giannini et al 22 using a novel PLT to spleen diameter ratio cutoff of 909, the diagnostic accuracy for GEV was 86% with a negative predictive value of 87%. The accuracy was maintained when the severity and etiology of the disease subgroups were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (21)(22)(23)(24)(25) have been performed in an attempt to validate this new parameter as a new noninvasive screening tool for EVs.…”
Section: Discussionmentioning
confidence: 99%
“…This versatile use of platelet count and thrombocytopenia is supported by the multi-faceted etiology of decreased platelet count in chronic liver disease patients [1,5]. Indeed, the platelet count is incorporated into numerous diagnostic algorithms aimed at non-invasively assessing the severity of chronic liver diseases and features of portal hypertension, can be used to pinpoint patients at higher risk of developing hepatocellular carcinoma in population studies, and is a predictor of death in cirrhotic patients with and without hepatocellular carcinoma [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%